Description of Antihypertensive Medication Use in a Pediatric Practice: Single and Multiple Antihypertensive Medication Therapy. Issue 1 (2nd August 2016) - Binka, Edem; Mendley, Susan; Gaskin, Peter; Himes, Carisa; Jinadu, Laide; Baker‐Smith, Carissa M.
Abstract : Prescription of multiple antihypertensive medications for the treatment of essential hypertension (HTN) has been well described in adults but not in children and adolescents. The authors describe the frequency with which children with essential HTN are prescribed a single vs two or more concomitantly administered antihypertensive medications. They also describe demographic features and comorbidities associated with the prescription of a single vs multiple antihypertensive medications. Multiple antihypertensive medication use in the management of pediatric HTN, as in the management of adult HTN, is not uncommon. In this single‐center, retrospective study of 113 children with essential HTN, 28% of children were concomitantly prescribed two or more antihypertensive medications for poorly controlled blood pressure following prescription of a single medication. Demographic and comorbid conditions associated with the prescription of more than one antihypertensive medication include advanced hypertensive stage, race, and a family history of HTN.